If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -9x = 45 + -23x Solving 5 + -9x = 45 + -23x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '23x' to each side of the equation. 5 + -9x + 23x = 45 + -23x + 23x Combine like terms: -9x + 23x = 14x 5 + 14x = 45 + -23x + 23x Combine like terms: -23x + 23x = 0 5 + 14x = 45 + 0 5 + 14x = 45 Add '-5' to each side of the equation. 5 + -5 + 14x = 45 + -5 Combine like terms: 5 + -5 = 0 0 + 14x = 45 + -5 14x = 45 + -5 Combine like terms: 45 + -5 = 40 14x = 40 Divide each side by '14'. x = 2.857142857 Simplifying x = 2.857142857
| 6x+39=16x-42 | | 5x+20=10x+10 | | 3(w-2)=12 | | 6a=17.4 | | 2a(3a-2)=0 | | 208-4x=32+20 | | t(4t-7)=0 | | 30+30*0+1=1 | | 5x-6=10x-16 | | 2x+36=12x-74 | | 7x-9=4x+12 | | =(6z^9-5z^4+4z^2+6)+(7z^7+4z^4-6z) | | 5x+7=77-7x | | 7x-2x=12 | | 3u+20=8u | | 6x+13=-9-10 | | 7g-15=g-3 | | 2x+x^2+144=0 | | 85-3x=2x+10 | | (4-2k+3l)+(2-3k-2l)= | | 135-2x=34x+15 | | -104-7x=10x+15 | | 2x+12=-38-8x | | y=-32x^2-6x | | y=-32x^2-6x | | y=-32x^2-6x | | 2x^2+30=0 | | 14-10x=74-24x | | -37-7x=7x+20 | | (7z-3)-(4z-11)=47 | | 6t-5=2t-5 | | 266-6x=39x+21 |